A quasi-review of conceptual flotation design methods based on computational optimization. (March 2018) - Cisternas, Luis A.; Lucay, Freddy A.; Acosta-Flores, Renato; Gálvez, Edelmira D.
Graphical abstract: Highlights: Superstructures, mathematical models, and optimization algorithms are reviewed. The effect of epistemic and stochastic uncertainties on design are discussed. The gaps of the methods for implementation in plant design are identified. The benefits and barriers of optimization based methods are highlighted. Abstract: This paper presents a review and analysis of the research applying optimization to flotation design problems. Specifically, superstructures utilized, mathematical models, and optimization algorithms. The effect of epistemic and stochastic uncertainties are discussed. The new knowledge generated using this type of techniques are highlighted. As these techniques are not used in practice, the gaps for implementation are identified. The review leads to conclusions regarding the benefits of optimization based methods in practice and barriers to their use. Likely future developments are discussed.